Electrochemical enantiorecognition of tryptophan enantiomers based on a multi-walled carbon nanotube–hydroxyethyl chitosan composite film. Issue 35 (22nd August 2017) - Li, Zhenliang; Mo, Zunli; Guo, Ruibin; Meng, Shujuan; Wang, Ruijuan; Gao, Huhu; Niu, Xiaohui
Abstract : A novel chiral electrochemical sensor based on hydroxyethyl chitosan (HECS) covalently binding with the carboxylic multi-walled carbon nanotubes (MWCNT–COOH) was fabricated for discrimination of tryptophan (Trp) enantiomers. Abstract : A novel chiral electrochemical sensor based on hydroxyethyl chitosan (HECS) covalently binding with the carboxylic multi-walled carbon nanotubes (MWCNT–COOH) was fabricated for discrimination of tryptophan (Trp) enantiomers. HECS preferably combined withl -Trp than withd -Trp because of the favorability of host–guest interactions between HECS and Trp enantiomers. Thus, the recognition efficiency was remarkably improved after hydroxyethyl groups were grafted onto chitosan (CS); this might be attributed to the formation of hydrogen bonds between Trp enantiomers and HECS. In addition, the small stereo-hindrance effect could play an important role in enantioselective discrimination.